PENGARUH PENGENDALIAN INTERNAL, SASARAN ANGGARAN, DAN KUALITAS SUMBER DAYA MANUSIA TERHADAP KINERJA ORGANISASI - Maanary, Audryan Novalino; Handayani, Nur (Jurnal Ilmiah Akuntansi dan Keuangan (JIAKu), 2023)
This research aimed to examine and identify the effect of internal control, budget targets, and human resource quality on the church organization’s performance in Sidoarjo (GPIB). The population was leader or active pastor, active assembly, active management in the servant category, and church employees in Sidoarjo (GPIB Bethesda, GPIB Tiberias, and GPIB Shalom). Moreover, the research was quantitative. The data collection technique used purposive sampling, in which the sample was based on the criteria given. In line with that, there were 96 respondents as the sample. Furthermore, the data were primary. The data analysis technique used multiple linear regression with SPSS (Statistical Product and Service Solution) 29 version. The result of the data which were collected and analyzed showed that internal control had a positive effect on the church organization's performance. Similarly, budget targets had a positive effect on the church organization's performance. Likewise, human resource quality had a positive and significan effect on the church organization’s performance.